Imaging features of hematogenous metastases to the pancreas: pictorial essay - Heng Tan, Cher (e-Med, 2011)
This pictorial essay illustrates the imaging appearances of a wide variety of metastases to the pancreas as seen on computed tomography (CT), magnetic resonance imaging and positron emission tomography/CT. Key clinical and radiologic features (lesion distribution, non-contrast imaging appearance, enhancement pattern and pattern of spread) that may aid differentiation of primary from solitary secondary pancreatic malignancies are discussed.